Internet-based aftercare for patients with personality disorders and trauma-related disorders: A pilot study. (March 2020) - Bilić, Sally Sophie; Moessner, Markus; Wirtz, Gustav; Lang, Stephan; Weisbrod, Matthias; Bauer, Stephanie
Highlights: First study investigating the feasibility and acceptability of an Internet-based aftercare program for patients with personality disorders (PD) and trauma-related disorders following psychiatric discharge. The study and the intervention were conducted within routine care. Uptake rate among patients was high as well as their acceptance of and satisfaction with the intervention. The intervention may be a beneficial offer in the transition phase after discharge with regard to the maintenance of treatment gains. Abstract: Preventing readmission after hospital discharge is a major issue with regard to the continuity of patients' recovery process and the financial burden on the healthcare system, but adequate aftercare services are lacking. Therefore, a pilot study was conducted to examine the feasibility and acceptability of an Internet-based aftercare program for patients with personality disorders (PD) and / or trauma-related disorders as well as to obtain a preliminary estimate of effects on symptomatology and readmission. Patients' satisfaction with the program and symptomatology (KPD-38, BDI-II) were assessed prior to hospital discharge (t1 ) and after three months of participation (t2 ). Log data on program utilization (i.e., logins, page hits, and chat use) were automatically assessed via server logs. N  = 31 of 45 eligible patients consented to participate. 84% used the intervention at least once. The average duration of participation was 63 days (SD = 4.6). Patients attended on average 7.2 out of 12 group chat sessions (SD = 4.0). Findings indicate very high acceptance of and satisfaction with the intervention. Symptomatology on all outcomes was stable, no deteriorations could be observed. 20% reported readmission within the aftercare period. Efficacy and cost-effectiveness should be tested with a large-scale randomized controlled trial.